Building information modelling (BIM) as a project management tool - Hedans Karuppiah, 1982-, author; Abdul Rahim Abdul Hamid, supervisor; Fakulti Kejuruteraan Awam (2014)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2014